Couple-Youth Attachment and Demand Withdraw Communication Pattern in the Relationship - Fatahyah, Yahya; Nur Fatihah, Mat Yusoff; Ahmad Tarmizi, Talib; Abdul Hakim, Mohad (IYRES, 2015)
An attachment relationship refers to a tie of affection that bonds someone with an attachment figure, principally the primary caregiver. Attachment styles and the quality relationships are determined partly as the result of mental images of both the self and others. Individuals who sensed that they were being rejected as children may develop insecure attachment relationships with significant people in their later life. In contrast, individuals who had positive experiences of relationships may develop a sense of security that allows them to seek such relationships in the future. This study aimed to explore the influence of couple-youth attachment on relationship quality related to demand and withdraw communication pattern in the relationship. A correlational research design was used to address the research objective. One hundred and fifty three (153) youth participants were employed. Two established questionnaires were used: Experience in Close Relationship and Communication Pattern Questionnaire. The results showed that youth couples with highly avoidance in attachment reported greater conflict demand and withdraw communication in the relationship.